Inovasi Asesmen Pendidikan Agama Islam Berbasis Teknologi Digital dan Deep Learning dalam Meningkatkan Higher Order Thinking Skills Peserta Didik - Ahmad Salim Ulul Albab; Moh. Sahlan (4, 2026)
The development of digital technology has driven the transformation of various aspects of education, including learning assessment systems. Islamic Religious Education (PAI) is required to develop assessment models that not only measure mastery of religious material but also enhance students' Higher Order Thinking Skills (HOTS). This study aims to analyze innovations in Islamic Religious Education assessments based on digital technology and deep learning in improving students' HOTS. The study employed library research with a descriptive qualitative approach. Data were obtained through a review of various literature sources, including books, scientific journals, articles, proceedings, and relevant documents related to digital assessment, deep learning, Islamic Religious Education, and HOTS. Data analysis was conducted using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The study results indicate that digital technology-based assessments facilitate learning evaluation through the use of digital platforms, Learning Management Systems (LMS), e-portfolios, interactive quizzes, and various learning applications, enabling an effective, flexible, and sustainable assessment process. Meanwhile, the deep learning approach encourages students to deeply understand Islamic concepts, engage in critical reflection, connect knowledge to the realities of life, and develop analytical, evaluation, and creative skills. The integration of digital technology and deep learning results in an assessment model that is more authentic, contextual, and oriented toward developing HOTS (Highest Level of Understanding). In addition to enhancing critical thinking and problem-solving skills, this assessment innovation also contributes to strengthening students' religious character, ethics, and social responsibility. Abstrak. Perkembangan teknologi digital telah mendorong transformasi berbagai aspek pendidikan, termasuk dalam sistem asesmen pembelajaran. Pendidikan Agama Islam (PAI) dituntut untuk mengembangkan model asesmen yang tidak hanya mengukur penguasaan materi keagamaan, tetapi juga mampu meningkatkan kemampuan berpikir tingkat tinggi atau Higher Order Thinking Skills (HOTS) peserta didik. Penelitian ini bertujuan untuk menganalisis inovasi asesmen Pendidikan Agama Islam berbasis teknologi digital dan deep learning dalam meningkatkan HOTS peserta didik. Penelitian menggunakan metode library research dengan pendekatan kualitatif deskriptif. Data diperoleh melalui kajian berbagai sumber literatur berupa buku, jurnal ilmiah, artikel, prosiding, dan dokumen relevan yang berkaitan dengan asesmen digital, deep learning, Pendidikan Agama Islam, dan HOTS. Analisis data dilakukan menggunakan teknik content analysis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil kajian menunjukkan bahwa asesmen berbasis teknologi digital memberikan kemudahan dalam pelaksanaan evaluasi pembelajaran melalui penggunaan platform digital, Learning Management System (LMS), e-portfolio, kuis interaktif, dan berbagai aplikasi pembelajaran yang memungkinkan proses penilaian berlangsung secara efektif, fleksibel, dan berkelanjutan. Sementara itu, pendekatan deep learning mendorong peserta didik untuk memahami konsep keislaman secara mendalam, melakukan refleksi kritis, menghubungkan pengetahuan dengan realitas kehidupan, serta mengembangkan kemampuan analisis, evaluasi, dan kreasi. Integrasi teknologi digital dan deep learning menghasilkan model asesmen yang lebih autentik, kontekstual, dan berorientasi pada pengembangan HOTS. Selain meningkatkan kemampuan berpikir kritis dan pemecahan masalah, inovasi asesmen ini juga berkontribusi terhadap penguatan karakter religius, etika, dan tanggung jawab sosial peserta didik.